Antenatal tobacco use and iron deficiency anemia: integrating tobacco control into antenatal care in urban India - Ritesh Mistry; Andrew D. Jones; Mangesh S. Pednekar; Gauri Dhumal; Anjuli Dasika; Ujwala Kulkarni; Mangala Gomare; Prakash C. Gupta (BMC, 2018)
Abstract Background In India, tobacco use during pregnancy is not routinely addressed during antenatal care. We measured the association between tobacco use and anemia in low-income pregnant women, and identified ways to integrate tobacco cessation into existing antenatal care at primary health centers. Methods We conducted an observational study using structured interviews with antenatal care clinic patients (n = 100) about tobacco use, anemia, and risk factors such as consumption of iron rich foods and food insecurity. We performed blood tests for serum cotinine, hemoglobin and ferritin. We conducted in-depth interviews with physicians (n = 5) and auxiliary nurse midwives (n = 5), and focus groups with community health workers (n = 65) to better understand tobacco and anemia control services offered during antenatal care. Results We found that 16% of patients used tobacco, 72% were anemic, 41% had iron deficiency anemia (IDA) and 29% were food insecure. Regression analysis showed that tobacco use (OR = 14.3; 95%CI = 2.6, 77.9) and consumption of green leafy vegetables (OR = 0.6; 95%CI = 0.4, 0.9) were independently associated with IDA, and tobacco use was not associated with consumption of iron-rich foods or household food insecurity. Clinics had a system for screening, treatment and follow-up care for anemic and iron-deficient antenatal patients, but not for tobacco use. Clinicians and community health workers were interested in integrating tobacco screening and cessation services with current maternal care services such as anemia control. Tobacco users wanted help to quit. Conclusion It would be worthwhile to assess the feasibility of integrating antenatal tobacco screening and cessation services with antenatal care services for anemia control, such as screening and guidance during clinic visits and cessation support during home visits.